Global landscape of space weather observations, research and operations - Mamoru Ishii; Joaquim E.R. Costa; Maria Kuznetsova; Mario M. Bisi; Amalia Meza; Astrid M. Veronig; Clezio Marcos Denardini; Christina Plainaki; Sergio Dasso; Manuela Temmer; María Graciela Molina; Jens Berdermann; et al. (Advances in Space Research, 2025)

Earth’s geomagnetic environment—progress and gaps in understanding, prediction, and impacts - Hermann J. Opgenoorth; Robert Robinson; Chigomezyo M. Ngwira; Katherine Garcia Sage; Maria Kuznetsova; Mostafa El Alaoui; David Boteler; Jennifer Gannon; James Weygand; Viacheslav Merkin; Katariina Nykyri; Burcu Kosar; et al. (Advances in Space Research, 2024)

Borderless conservation: Integrating connectivity into high seas conservation efforts for the Salas y Gómez and Nazca ridges - Ben Boteler; Daniel Wagner; Carole Durussel; Emily Stokes; Carlos F. Gaymer; Alan M. Friedlander; Daniel C. Dunn; Felipe Paredes Vargas; David Veliz; Carolina Hazin (Frontiers in Marine Science, 2022)
Connectivity is essential to consider in area-based marine conservation measures because it greatly impacts vital ecological processes (e.g., recycling nutrients, regulating temperature, sequestering carbon, and supporting the life cycle of species). However, it is generally not well studied or integrated into conservation measures, particularly in the Southeast Pacific. This region is home to the Salas y Gómez and Nazca ridges, two adjacent seamount chains that stretch between the Peruvian coast and Rapa Nui (i.e., Easter Island). The area has been recognized for its exceptional natural and cultural significance as well as one of the most important global areas to protect. However, over 73% of the ridges are in areas beyond national jurisdiction, where they are unprotected and under threat. This study provides a synthesis of what we know about connectivity in the Salas y Gómez and Nazca ridges and provides practical recommendations for integrating this knowledge into conservation and management measures for the region. While data on connectivity is still limited, it should not constrain the development of conservation measures, which should be co-designed and co-developed, leveraging the expertise of international working groups throughout the region. Due to their high rates of endemism, as well as importance as migratory corridors, enacting large-scale conservation measures would address important conservation considerations for both connectivity and endemism. Enacting such large-scale conservation measures would not only elevate the Salas y Gómez and Nazca ridges as an exemplary case study, providing lessons for other marine regions seeking to implement similar measures, but could also help raise awareness on the severity of externally originating threats like climate change and plastic pollution to global audiences.